Impacto de las grandes tiendas comerciales en las pymes del centro comercial El Virrey – Trujillo 2011 - Lavado Mendocilla, Lourdes Mercedes (2013)
In this, we conducted applied research to SMEs that exist in the city of Trujillo, whose competition affects consumer wholesale of clothing and footwear, many small businesses like supermarkets to small and medium enterprises. In this study we want to know the impact and positioning of the department stores in SMEs Commercial Shopping Center "The Viceroy" consumer characteristics of SMEs and finally Geomarketing Location by consumers who shop at the Mall "the Viceroy" Trade and the Department Stores. Likewise consumers decide where to shop, get their attention, special offers and discounts, as sales of the workers have been affected over the department stores, but their businesses continue to grow compared to the beginnings of the department stores and improved in quality of service, practicing strategies, improved the ambience, service, consumer loyalty also. The population is made up of SMEs (Small and Medium Enterprises) dedicated to the category of adult clothing - kids shoes Consumers also are the people who shop in SMEs. The installation of SMEs remains the same with customers has declined in the business of locating workers and consumers made their purchases in SME and Commercial Center